Closing Time: Open Records Law and College Athletics - White, Scott (Journal of Intercollegiate Sport, 2024)
Open records laws have a significant impact on how college athletic departments operate and compete. This paper examines the current state of open records laws in relation to college athletics departments. The central finding is that the current set of incentives creates an untenable “race to the bottom” which undermines the public policy goals of open records laws. The topic of open records laws is significant for athletics department employees and other stakeholders. The foundational principles underlying open records laws can be traced back to the founding of the United States and are a critical aspect of democracy. However, athletic departments use a variety of tactics to avoid or delay providing documents in response to public records requests, and these tactics vary by state and institution. The incentives faced by coaches and athletics directors contribute to a situation where these stakeholders and lawmakers advocate for policy changes that ultimately undermine the public’s ability to access records relating to intercollegiate sport. The solution to this problem will require cooperation across states to enact a set of model rules that will level the playing field and restore the public’s ability to access documents produced by college athletics departments.